Дослідження режимів та ідентифікація параметрів моделі системи наведення та стабілізації бойових машин - Паранчук, Ярослав Степанович; Мороз, Володимир Іванович; Євдокімов, Павло Миколайович; Карплюк, Леонід Федорович (НТУ "ХПІ", 2013)
The variant of the computer model of the electric drive of the multiple rocket launcher guides is proposed in this article. The identification of the mechanical parts of drive based on experimental data's including their features such as Coulomb and viscous friction and springiness of the guides mechanism was used for model description.
Regimes research and model parameters identification of the servo and stabilize systems of the military vehicles
Keywords: мобільні системи електроприводу; механізм наведення; реактивний момент статичного навантаження; ідентифікація параметрів електроприводу